Assessing the impacts of organic and inorganic contaminants on British rivers: from sediments to fish - Ramage, Calum (2024)
Human activity is responsible for the release of harmful levels of environmental contaminants into the environment, with pesticides and trace elements amongst the most prevalent. Rivers are particularly vulnerable to the accumulation of chemical pollutants, posing significant health risks to local aquatic wildlife. However, relatively little is known about their presence, distribution, and impacts on UK aquatic ecosystems. This study aimed to assess the environmental impacts of trace element and pesticide pollution in English rivers, focusing on their environmental distribution, bioaccumulation in aquatic wildlife, and associated risks, particularly to fish.